Jewish Enlightenment in an English Key : Anglo-Jewry's Construction of Modern Jewish Thought - Ruderman, David B. (Book collections on Project MUSE., 2000)
This portrait of English Jews reformulating their tradition in light of Enlightenment categories illuminates an overlooked corner in the history of Jewish culture in England and Jewish thought during the Enlightenment."--Jacket